FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT ADOPSI PETANI MANGGIS TERHADAP GOOD AGRICULTURE PRACTICES (GAP) DI KECAMATAN KOTA AGUNG KABUPATEN TANGGAMUS - Azil Agustino; Indah Nurmayasari; Begem Viantimala (Lampung University, 2020)
The purposes of this research are to analyze farmers adoption level on Good Agriculture Practices (GAP), factors related to the adoption level, and the constraints faced by farmers in the implementation of Good Agriculture Practices (GAP). This research was conducted in Kota Agung subdistrict of Tanggamus district, by interviewing 74 respondents, mangosteen farmers who joined and applied Good Agriculture Practices (GAP) at Kota Agung. Data were collected using a survey method with descriptive analysis and Rank Spearman correlation test to examine hypothesis. The results showed that adoption level of mangosteen farmers on GAP is included on a medium classification (64,86%), the factors related are experience of farming, formal education level, characteristics of innovation, and level of cosmopolite characteristic, while the unrelated factors are land area and capital availability. The constraints faced are unpredictable weather conditions, pests and plant diseases, price determination by traders, lack of information and knowledge of Good Agriculture Practices (GAP), and unpublished Good Agriculture Practices (GAP) land registration number in Penanggungan village.Key words: adoption level, good agriculture practices (GAP), mangosteen farmers